Effects of lemon essential oil and limonene on the progress of early caries: An in vitro study. (March 2020) - Ma, Li; Chen, Jing; Han, Hui; Liu, Peiwen; Wang, Huijuan; Lin, Shiyi; Zhang, Qin; Lu, Danyang; Zhang, Xiangyu
Highlights: LEO and LIM have positive effects on the progress of early caries. LEO and LIM can inhibit collagen degradation to stabilize its structure. It is the first study of the effects of LEO and LIM in terms of mineralization. This may be beneficial to the prevention and treatment of initial root caries. Abstract: Objective: The purpose of this study was to investigate the effects of Lemon essential oil (LEO) and Limonene (LIM) in the progress of early caries. Design: LEO and LIM were selected as experimental medicine, while sodium fluoride (NaF) and deionized water (DW) were positive and blank controls, respectively. Bovine incisors were used to establish enamel and dentin early caries models by demineralization method in vitro. Then specimens were subjected to pH cycling. Calcium and phosphate release of demineralizing solution were measured by an automatic biochemical analyzer; Surface microhardness tester and energy dispersive X-ray spectrometer were used to detect the surface microhardness recovery and calcium- phosphate ratio on tooth surface; Degraded collagen matrix by collagenase was investigated by assaying hydroxyproline. Results: Calcium release of dentin demineralizing solution of LEO group was lower than DW group's and higher than NaF group's. Both of LEO and LIM groups, the surface microhardness recovery were significantly lower than those of NaF group, which were similar to DW group. Dentin surface calcium- phosphate ratio of LEO and LIM groups were lower than those of NaF group and higher than those of DW group. Hydroxyproline concentration in the remineralizing solution of LEO and LIM groups were lower than DW groups' and higher than NaF groups'. Conclusions: LEO and LIM have influence on the progress of dentin early caries, which can stabilize its structure by inhibiting collagen degradation. Meanwhile, these medicines may provide a new drug choice for the prevention and treatment of early root caries.